Talking Donald Trump: A Sociolinguistic Study of Style, Metadiscourse, and Political Identity - Karlina Denistia (Masyarakat Linguistik Indonesia, 2019)
ISBN : 978-1-138-24450-4 (hbk)ISBN : 978-1-3152-7688-5 (ebk)Penulis : Jennifer SclafaniPenerbit : Routledge (2018)Tebal : 105 halaman